2020
DOI: 10.3389/fmars.2020.00629
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With Governance in Three Marine Conservation Zoning Initiatives: Parameters for Assessment and Pathways Forward

Abstract: In this perspective paper, we examine the challenges of governance in three marine conservation settings where rights, access to resources and zoning intersect with changing social and ecological conditions: (1) Tsitsikamma Marine Protected Area in South Africa; (2) Marine Protected Area of the Northern Coast of São Paulo (APAMLN) in Brazil; and (3) Gwaii Haanas National Marine Conservation Area Reserve in Canada. Many MPAs and related zoning initiatives are located adjacent to coastal communities that rely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…The meaningful inclusion of indigenous and local communities in MSP not only decreases the odds of system sabotage (Msomphora, 2016;Metcalfe et al, 2018), but also allows the exchange of information and acceptance of new knowledge systems and distinct worldviews (Armitage et al, 2011). The effectiveness of conservation or any regulation is contingent on compliance (Arias et al, 2015), as clearly demonstrated in fisheries in general and in the assessment of the ecological performance of marine protected areas (Bergseth et al, 2015;Muhl et al, 2020). By promoting engagement, responsibility sharing and empowerment of all stakeholders in decision-making, greater compliance, lower surveillance costs (Freitas et al, 2020), and changes in the levels and types of information and knowledge exchanged are expected.…”
Section: The Missing Layers: Sociocultural Values and Underrepresented Groups Rightsmentioning
confidence: 99%
“…The meaningful inclusion of indigenous and local communities in MSP not only decreases the odds of system sabotage (Msomphora, 2016;Metcalfe et al, 2018), but also allows the exchange of information and acceptance of new knowledge systems and distinct worldviews (Armitage et al, 2011). The effectiveness of conservation or any regulation is contingent on compliance (Arias et al, 2015), as clearly demonstrated in fisheries in general and in the assessment of the ecological performance of marine protected areas (Bergseth et al, 2015;Muhl et al, 2020). By promoting engagement, responsibility sharing and empowerment of all stakeholders in decision-making, greater compliance, lower surveillance costs (Freitas et al, 2020), and changes in the levels and types of information and knowledge exchanged are expected.…”
Section: The Missing Layers: Sociocultural Values and Underrepresented Groups Rightsmentioning
confidence: 99%
“…One of the critical steps in the MPA implementation process is the design of management zones 10 , 11 , which afford varying levels of restriction of human use within their boundaries. The establishment of multiple zones within an MPA can improve their overall effectiveness by minimizing social conflict between activities 12 , accommodate a myriad of conservation objectives in the planning process 5 , and optimize associated biodiversity and fishery benefits 11 , 13 , 14 . The science of conservation planning emphasizes the use of decision support tools to help identify the optimal spatial arrangement of zones 15 , which requires an understanding of the spatial distribution of habitats and species.…”
Section: Introductionmentioning
confidence: 99%
“…The science of conservation planning emphasizes the use of decision support tools to help identify the optimal spatial arrangement of zones 15 , which requires an understanding of the spatial distribution of habitats and species. Ideally, there will be also a large understanding of social and cultural context, and the integration of stakeholder’s perception into the zoning design process 14 , 16 . A robust design of management zones encompasses detailed information on biodiversity distribution and spatial representation of local uses, such as fishing and tourism, to identify areas where management actions are required while allowing human activities (i.e., multiple-use areas), and areas that are fully protected from all extractive and human uses (i.e., no-take areas) 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Connectivity, leading to dispersal and recruitment, is a major paradigm to delineate MPAs since spillover is the most desirable ecosystem service from marine reserves (Brown et al 2016;Bryan-Brown et al 2017;White et al 2019). In tropical coastal areas, the adaptive capacity of local communities, together with opportunities for co-management, greatly improve governance and effectiveness of MPAs (Camargo et al 2009;Moreno-Sánchez and Maldonado 2010;López-Angarita et al 2014;Kockel et al 2019;Muhl et al 2020). In any case, marine ecosystems face threats due to global warming and ocean acidi cation, where the traditional management tools do not seem to buffer deterioration (Hoegh-Guldberg and Bruno 2010; Jackson et al 2014;Pendleton et al 2016;Hoegh-Guldberg et al 2017).…”
Section: Introductionmentioning
confidence: 99%